1984
DOI: 10.1111/j.1744-313x.1984.tb00819.x
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Recognition of Lysozyme Iv. Localization and Genetic Control of the Continuous T Cell Recognition Sites by Synthetic Overlapping Peptides Representing the Entire Protein Chain

Abstract: SUMMARY Recently, this laboratory has developed a comprehensive strategy for the systematic localization of all the ‘continous’ antigenic (as well as other binding) sites of complex multivalent protein antigens involved in B and T cell recognition. The strategy depends on the syntheis of consecutive overlapping peptides that together account for the entire protein chain. This strategy was applied here for the localization of the ‘continuous’ T cell recognition sites of hen egg lysozyme. Eight overlapping pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…The results reported here show that LNCs whose specificity is directed against a region [a- (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)] that is completely buried within the subunit association surfaces in Hb recognize the free synthetic peptide and the isolated subunit but not the intact tetramer. LNCs against regions that are only partially involved in subunit association or against exposed regions that are not involved at all in subunit contacts recognize the peptide and the isolated subunit as well as intact Hb.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The results reported here show that LNCs whose specificity is directed against a region [a- (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)] that is completely buried within the subunit association surfaces in Hb recognize the free synthetic peptide and the isolated subunit but not the intact tetramer. LNCs against regions that are only partially involved in subunit association or against exposed regions that are not involved at all in subunit contacts recognize the peptide and the isolated subunit as well as intact Hb.…”
Section: Resultsmentioning
confidence: 80%
“…Several years ago, studies from this laboratory showed that T-cell epitopes on a protein very frequently overlap or coincide with B-cell epitopes that occupy exposed surface regions ofthe protein (10,11,(29)(30)(31)(32)(33)(34)(35). These regions, therefore, are prime targets for proteolysis and would be expected to be readily destroyed by processing (27,36).…”
Section: Resultsmentioning
confidence: 99%
“…Nine different HEL peptides reported to be restricted to either H-2 b , H-2 d or H-2 q MHC II haplotypes (11,32) were synthesized by the Stanford Peptide Synthesis Group. Three peptides, HEL 20 -35 restricted to H-2 b , HEL 106 -116 restricted to H-2 d , and HEL 93-113 restricted to H-2 q , were chosen based immunogenicity as assessed in lymph node proliferation assays of immunized untransplanted control mice.…”
mentioning
confidence: 99%
“…It is well established that, in the immune responses to a multi-determinant complex protein antigen, the responses to each determinant (both antibody and T cell) are under separate genetic control (Okuda et aL, 1979;Twining et a/, 1981;David and Atassi, 1982). In a given mouse strain, the regions on a protein antigen that are recognized by antibodies and * by T cells may coincide but there might also be regions on the protein that are recognized by antibodies and for which no detectable T-cell responses are found and/or conversely Tcell recognition regions for which no antibodies are detectable (Bixier and Atassi, 1983, 1984ab, 1985Atassi, 1984;Bixler et aL, 1984). In both Balb/c and SJL, peptides L1, 12 and C-tail were most protective against BgTX poise,t'Žng (PI: Balb/c, 3.2; SJL, 2.5-2.7).…”
Section: Discussionmentioning
confidence: 99%
“…For proliferative assay, single cell suspensions of LNC from primed mice were prepared in Hank's balanced salt solution. The cells were washed and resuspended in RPMI 1640 with 1% normal mouse serum and supplemented as described (Bixler et aL, 1984). The number of viable cells was determined by vital staining with fluorescein diacetate (Rotman and Papermaster, 1966 2.7.…”
Section: Radioimmunoadsorbent Titrations Of Anti-bgtx Antiseramentioning
confidence: 99%